2016
DOI: 10.3349/ymj.2016.57.6.1312
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of the M2 Isoform of Pyruvate Kinase (PKM2) with shRNA Enhances the Effect of Docetaxel in Human NSCLC Cell LinesIn Vitro

Abstract: PurposeThe aim of our study was to explore the relationships between the M2 isoform of pyruvate kinase (PKM2) and the sensitivity of human non-small cell lung cancer (NSCLC) cells to docetaxel in vitro.Materials and MethodsWith the method of plasmid transfection, we silenced the expression of PKM2 successfully in A549 and H460 cells. Western blotting and real-time PCR were applied to detect PKM2 expression at protein and gene levels. Cell viability was examined by CCK8 assay. Cell cycle distribution and apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…The M2 isoform (PKM2) is a key regulator of glycolysis, expressed only in cancer cells [ 165 ], and targeting this molecule can inhibit cell viability, induce G2/M arrest, and promote apoptosis. Additionally, this can increase the radiosensitivity of NSCLCs and the IR-induced apoptosis and autophagy rates, which are associated with the inhibition of AKT and PDK1 phosphorylation [ 166 ]. PKM2 is targeted by miR-133 as well, and this miRNA is downregulated in radioresistant lung cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…The M2 isoform (PKM2) is a key regulator of glycolysis, expressed only in cancer cells [ 165 ], and targeting this molecule can inhibit cell viability, induce G2/M arrest, and promote apoptosis. Additionally, this can increase the radiosensitivity of NSCLCs and the IR-induced apoptosis and autophagy rates, which are associated with the inhibition of AKT and PDK1 phosphorylation [ 166 ]. PKM2 is targeted by miR-133 as well, and this miRNA is downregulated in radioresistant lung cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, elevated expression of PKM2 is involved in cell proliferation and tumourigenesis, as well as the regulation of immune and inflammatory responses. More importantly, accumulating evidence has suggested that enhanced PKM2 expression correlates with therapeutic resistance in LUAC (Meng et al, 2015;Yuan et al, 2016). Furthermore, selective inhibition or knockdown of PKM2 with RNAi leads to suppression of cell proliferation, induction of apoptosis and increase of the sensitivity of tumor cells to chemotherapy in LUAC, suggesting that selective targeting of PKM2 may serve as a potential therapeutic target for LUAD, especially for patients with chemotherapeutic resistance (Chu et al, 2015;Sun et al, 2015;Suzuki et al, 2019;Wang et al, 2019;Yuan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In NSCLC, Yuan et al, suggested that PKM2 knockdown could serve as a chemosensitizer to docetaxel, leading to the inhibition of cell viability, cell cycle arrest at G2/M phase and apoptosis [221]. These results further suggest that application of targeting the PKM2 has the potential to be a therapeutic strategy for NSCLC and provides one possible way to improve the chemotherapy effect of docetaxel.…”
Section: New Therapies a Comprehensive Adjustment Of Therapy To Thementioning
confidence: 99%